COMMENTS ON THE AUDITS OF SCHOOL DISTRICTS. - Schaefer, Hadley P. (The Accounting Review, 1957)
The critical review and appraisal of school accounting records and procedures is an essential step in the continuing development of more effective school administration. As school facilities and faculties grow, the school executive must rely on proven business techniques. The results produced by these techniques should be disclosed to interested parties. It is the auditor's function to consider whether the disclosures fairly reflect the results of school operations. It appears that each state has different audit requirements. A hopeful approach might be the establishment, by the accounting authorities in conjunction with education authorities, of auditing procedures and accounting principles for school districts.